Serum big endothelin-1 is a significant biomarker of arterial stiffness in patients undergoing coronary artery bypass grafting - Jin-You Jhan; Jian-Hong Lin; Kun-Ta Yang; Bang-Gee Hsu; Jui-Chih Chang (Scientific Reports)
Abstract In the patients receiving coronary artery bypass grafting (CABG), arterial stiffness is an independent predictor of disease-related mortality. Higher serum levels of big endothelin-1 (BigET-1) are associated with arterial stiffness. The present study aimed to determine the association between serum BigET-1 levels and arterial stiffness in patients undergoing CABG. A total of 90 patients undergoing CABG were enrolled in the study. Serum levels of BigET-1 are examined with a commercial sandwich enzyme immunoassay. If carotid–femoral pulse wave velocity (cfPWV) > 10 m/s, arterial stiffness is diagnosed. In the study cohort, 30 (33.3%) patients with arterial stiffness were older and had lower body mass index, higher rates of diabetes mellitus and hypertension, higher systolic and diastolic blood pressures, and higher serum BigET-1 levels compared to the controls. Multivariable logistic regression analysis revealed that serum BigET-1 > 1 pg/mL was an independent predictor of arterial stiffness (odds ratio 17.492, 95% confidence interval 2.728–112.147, p = 0.003). Multivariable linear regression analysis revealed that cfPWV significantly correlated with age (β = 0.238, adjusted R2 change = 0.043, p = 0.004), systolic blood pressure (β = 0.251, adjusted R2 change = 0.102, p = 0.002), and BigET-1 level (β = 0.533, adjusted R2 change = 0.387, p < 0.001). Increased serum BigET-1 levels were associated with arterial stiffness in patients undergoing CABG.